2010
DOI: 10.1002/ana.21982
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator in human muscle: Dysfunction causes abnormal metabolic recovery in exercise

Abstract: We speculate that a defect in sarcoplasmic reticulum CFTR Cl(-) channels could alter the electrochemical gradient, causing dysregulation of Ca(2+) homeostasis, for example, ryanodine receptor or sarco(endo)plasmic reticulum Ca(2+) adenosine triphosphatases essential to excitation-contraction coupling leading to exercise intolerance and muscle weakness in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 35 publications
4
69
0
1
Order By: Relevance
“…These findings and our current data contrast with the typical localization of CFTR to the plasma membrane of polarized epithelial and serous cells (27,33,34). We further localized CFTR to the SR in ASM cells, a finding consistent with earlier reports of CFTR localization to the SR in skeletal muscle cells (41,42). CF disease manifestations are typically related to loss of CFTR function at the plasma membrane in epithelial cells.…”
Section: /2supporting
confidence: 82%
“…These findings and our current data contrast with the typical localization of CFTR to the plasma membrane of polarized epithelial and serous cells (27,33,34). We further localized CFTR to the SR in ASM cells, a finding consistent with earlier reports of CFTR localization to the SR in skeletal muscle cells (41,42). CF disease manifestations are typically related to loss of CFTR function at the plasma membrane in epithelial cells.…”
Section: /2supporting
confidence: 82%
“…Resting muscle ATP values have not been previously reported in the CF or PCD populations. Whether the decreased ATP levels we have observed is primary (6,7,30,31) or secondary to a defect in CFTR in the muscles of patients with CF cannot be directly determined from the current data. It is important to note that the biological consequence of this relatively small difference is unclear.…”
Section: Discussionmentioning
confidence: 90%
“…A report has shown that an intrinsic alteration of function is linked to the absence of CFTR from skeletal muscle, leading to dysregulated calcium homeostasis, augmented inflammatory or atrophic gene expression signatures, and increased diaphragm muscle weakness (6). Our research team has recently demonstrated the expression of CFTR in human skeletal muscle (7). In addition, evidence suggests that impaired anaerobic performance (8), abnormal anaerobic metabolism (9), and decreased maximal muscle strength and power (10 -12) occurs in CF patients.…”
mentioning
confidence: 99%
“…The samples were fixed in 2.5% glutaraldehyde at 4°C for 24 h and a semi-thin sectioning approach was used to locate the area of interest before the samples were prepared as ultrathin sections as described previously (12). Ultrastructure was observed using a Hitachi H600 TEM (Hitachi, Tokyo).…”
Section: Transmission Electron Microscope (Tem) Examinationmentioning
confidence: 99%